ANALISIS PENJATUHAN HUKUMAN PIDANA OLEH HAKIM DALAM PERKARA TINDAK PIDANA KORUPSI (Studi Putusan Nomor 62/PID.SUS/PT KORUPSI/2014/PN.PTK) - PERMADI SYAHIDS PUTRA., S.Ik A.2021141064, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
AbstractThis thesis discusses the analysis of criminal sentencing by the judge in the corruption case (Study of Decision No. 62 / Pid.Sus / Pt Corruption / 2014 / Pn.Ptk). The method used in this research is the empirical normative approach. From the results of this thesis can be concluded that considerations of Criminal Justice dropped the lighter because the state finances can not be justified by the defendant relatively little in Decision No. 62 / PID.SUS / PT. CORRUPTION / 2014 / PN.PTK not appropriate for the purpose of preventing and combating Corruption in UUPTPK and also not to give deterrent effect to the Corruptor. This can be seen in the explanation UUPTPK and it is supported by both the theory of Interest Criminalization Criminalization of Interest absolute, relative and combined. Karenakan in Decision No. 62 / PID.SUS / PT. CORRUPTION / 2014 / PN.PTK not leave the prevention of crime by making criminal threats are severe enough to scare would-Â¬calon officials and provide improvements or education for criminals (Verbeterings Theorie) chief villain is given